Exploring the development challenges facing rural women in Matabeleland South, Zimbabwe - Ndhlovu, Gretchen Nokukhanya (Department of Social Development, 2015)
The objectives of the study are to explore how women assess their situation in Matabeleland South with regard to their socio-economic realities; to find out the individual and community circumstances that these rural women in the drought prone region find themselves in; to explore the most important development challenges in relation to the impacts of climate change, access to water, food insecurity, poverty, education and health facilities; to examine the survival strategies that rural women adopt in the present situation and to ascertain the recommendations they make to the government and Non Governmental Organisations to improve their situation.